Chronic Insulin Exposure does not Cause Insulin Resistance but is Associated with Chemo-resistance in Colon Cancer Cells - Baricevic, I.; Roberts, D. L.; Renehan, A. G. (Hormone and Metabolic Research, 2014)
Insulin resistance is an adaptive process in insulin-sensitive tissues characterised by reduced insulin receptor (IR) and insulin-receptor substrate (IRS)-1 expression, increased IRS-1 serine phosphorylation and attenuated downstream signalling. We tested whether this molecular phenotype prevails in cancer cells after long-term exposure to insulin. We characterised expression of IR-related molecules, IRS-1 phosphorylation and downstream signalling in a panel of 5 colon cancer cell lines at different insulin exposures: 15 min (100 nM), approximating to acute stimulation; 48 h (100 nM), used to demonstrate adaptive changes; and 12 weeks (20 nM; chronic insulin exposure, CIE), approximating to chronic hyperinsulinaemia. To assess clinical relevance, we determined IC50 values (increased indicating chemo-resistance) in the CIE-treated cells using oxaliplatin, SN38 (irinotecan) and 5-fluorouracil (5-FU). All colon cancer cell lines (HCT 116, HT-29, C32, CaCo2, LoVo) were sensitive to 15 min insulin exposure with increased phosphorylation of Akt, PRAS40 and p70-S6K. At 48 h, there was incomplete or absent features of insulin resistance. In CIE-treated cells, there was reduced IR expression, incomplete IRS-1 adaptation, lack of signalling pathway attenuation and contra-adaptive increases in IRS-1 tyrosine phosphorylation in several cell types. In CIE cells, there were multiple examples of increased IC50 values (2- to 100-fold) following 24-h treatment with oxaliplatin and SN38, but not with 5-FU. We concluded that CIE in colon cancer cells does not completely induce an insulin resistance molecular phenotype but is associated with chemo-resistance. Adaptive changes seen in insulin-sensitive non-neoplastic cells in response to long-term insulin may not extrapolate to neoplastic cells.
Keywords: insulin resistance; insulin receptor; insulin receptor substrate; colon cancer; chemo-resistance